Qualitative and Quantitative Phytochemical Screening of Azadirachta indica Juss. Plant Parts - Khanal, Sujata (International Journal of Applied Sciences and Biotechnology, 2021)
Azadirachta indica which is commonly known as neem plant has one of the most promising medicinal properties having a wide spectrum of biological activity. Fresh matured leaves, stem-bark and seeds of A. indica (neem) were collected, air dried and aqueous-extract was used to screen for some active chemical constituents. Phytochemicals of neem plant parts were extracted and screened both qualitatively and quantitatively. The screening of A. indica was carried out at Institute of Agriculture and Animal Science, Paklihawa Campus, Rupandehi in a quest to evaluate the phytochemicals. Among the qualitative tests done for the presence of secondary metabolites; alkaloids, saponins, terpenoids, flavonoids were found to present in all of the tested parts whereas steroids, polyphenols and tannins were present only in leaves and stem-bark. Glycosides and coumarins are absent in all of the tested parts. Quantitative screening was also done by using gravimetric method. Alkaloids were found in all the parts of A. indica with the highest amount of alkaloids were obtained in stem-bark (12.8%) and lowest in leaves (10.67%). Highest flavonoids percentage was revealed in leaves (13.8%) and lowest flavonoids in stem-bark (12.8%). Similarly, seeds (2.53%) contained saponins % while it was lowest in stem-bark (2.50 %). Terpenoids % were similar in both i.e. leaves and stem-bark (13.13%), whereas lowest in seeds (12.77%). More research on secondary metabolites will be helpful to the chemical industries to produce plant-based chemicals and minimize the environment degradation from different synthetic chemicals.Int. J. Appl. Sci. Biotechnol. Vol 9(2): 122-127.